Structural basis for +1 ribosomal frameshifting during EF-G-catalyzed translocation - Demo, Gabriel (Nat Commun, 2021)
Frameshifting of mRNA during translation provides a strategy to expand the coding repertoire of cells and viruses. How and where in the elongation cycle +1-frameshifting occurs remains poorly understood. We describe seven ~3.5-Å-resolution cryo-EM structures of 70S ribosome complexes, allowing visualization of elongation and translocation by the GTPase elongation factor G (EF-G). Four structures with a + 1-frameshifting-prone mRNA reveal that frameshifting takes place during translocation of tRNA and mRNA. Prior to EF-G binding, the pre-translocation complex features an in-frame tRNA-mRNA pairing in the A site. In the partially translocated structure with EF-G•GDPCP, the tRNA shifts to the +1-frame near the P site, rendering the freed mRNA base to bulge between the P and E sites and to stack on the 16S rRNA nucleotide G926. The ribosome remains frameshifted in the nearly post-translocation state. Our findings demonstrate that the ribosome and EF-G cooperate to induce +1 frameshifting during tRNA-mRNA translocation.